Clinical Results and Prognostic Factors for Outcomes of Valgus Femoral Osteotomy Combined with Chiari Pelvic Osteotomy for Osteoarthritis of the Hip - Katsufumi Uchiyama, MD, PhD; Mitsutoshi Moriya, MD; Kensuke Fukushima, MD; Takeaki Yamamoto, MD, PhD; Naonobu Takahira, MD, PhD; Masashi Takaso, MD, PhD (JBJS Open Access, 2017)
Background:. Surgeons have long debated whether advanced or end-stage osteoarthritis of the hip in young patients should be treated with total hip arthroplasty or osteotomy. We reviewed the intermediate-term clinical results of valgus femoral osteotomy combined with Chiari pelvic osteotomy (VCO) for advanced or end-stage osteoarthritis associated with severe acetabular dysplasia of the hip in young patients and analyzed prognostic factors related to conversion to total hip arthroplasty. Methods:. The study group included 54 hips in 50 patients (5 men and 45 women; average age at the time of surgery, 45.6 years). The minimum and average durations of follow-up were 10 and 17.6 years, respectively. The Japanese Orthopaedic Association hip score (JOA score) was used for clinical evaluation. The probability of survival of the VCO from the time of the operation until the end point of conversion to total hip arthroplasty was calculated with use of the Kaplan-Meier method. We defined prognostic factors of outcome (conversion to total hip arthroplasty) with the Cox proportional hazards model. Results:. The mean total JOA score increased from 53.0 points preoperatively to 77.1 points at 1 year postoperatively, 81.6 points at 5 years, and 76.8 points at 10 years. The survival rates were 83.3%, 59.7%, and 46.9% at 10, 15, and 20 years, respectively. On univariate and multivariate analyses, patients with a low degree of acetabular roof obliquity had better postoperative results. Conclusions:. VCO is a surgical approach that preserves joint function in young patients with advanced or end-stage osteoarthritis associated with severe acetabular dysplasia of the hip. The postoperative prognosis of VCO was improved in patients with a low degree of acetabular roof obliquity. Level of Evidence:. Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.